THE POSSIBILITIES OF E-LEARNING TECHNOLOGY IN THE STUDY OF MATHEMATICAL ANALYSIS - Perkova, Natalia; Veselova, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The course of mathematical analysis is important in the subject preparation of computer science students. The article deals with the issues of improving the level of mathematical competence of students in the study of mathematical analysis using e – learning technology based on the learning environment of the European system of distance learning (Learning Management System-LMS) Moodle. The principles of selection of theoretical and practical content of the electronic course in mathematical analysis are described. The efficiency of the use of the developed training course as an auxiliary didactic tools. The experimental work was attended by students of the 1st course of the direction "Applied Informatics". The article presents some results of the use in the educational process of the electronic course in the process of mastering the discipline "Mathematical analysis".